Taliban talks: Past present and prospects for the US, Afghanistan and Pakistan - Mona Kanwal Sheikh; Maja Touzari Janesdatter Greenwood (Danish Institute for International Studies (DIIS), 2013)
This report takes stock of the burgeoning efforts to achieve some level of reconciliation with the Taliban after more than 11 years of war. It deals with the recent history of initiatives to engage with the Taliban, outlines the challenges to these initiatives and derives some recommendations for how to move forward with the peace processes. The first part written by Mona Kanwal Sheikh gives a brief background to, and status overview of the different initiatives that the US, Afghanistan and Pakistan have taken in order to initiate a peace process with the Taliban. Quoting extracts from recent interviews with experts from Afghanistan and Pakistan who have followed the different initiatives on peace and reconciliation closely, the second part identifies the challenges to the present situation and initiatives. The final part, written by Afghanistan analyst Tim Foxley, puts forward some thought-provoking recommendations on how to create a communication environment that can serve as a foundation for a viable peace process.
Keywords: 300